2018
DOI: 10.1021/acssuschemeng.8b03517
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Metal-Free Porous Organic Framework Heterogeneous Catalyst for Efficient CO2 Conversion under Mild and Cocatalyst-Free Conditions

Abstract: To reduce the ever-growing greenhouse gas CO 2 , CO 2 utilization is considered with much more promise as it could convert CO 2 into value-added industrial products and achieve carbon cyclic utilization. Therefore, a high performance catalyst is supposed to be an important prerequisite to achieve CO 2 activation and conversion. In this work, a new metal-free bifunctional porous organic framework (POF) heterogeneous catalyst, POF-PNA-Br − , has been successfully prepared with a two-step method. Because of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…The existence of imidazolinium‐based ionic moieties is confirmed by the bands at 1670 and 1560 cm −1 , which are typical C=N stretching vibrations of imidazole . The band at 1719 cm −1 in the IR spectrum of I COOH HCP is ascribed to the characteristic C=O stretching vibration of the carboxyl group . The enhanced band at 3388 cm −1 in the IR spectrum of I OH HCP may include the contribution of surface OH groups and the adsorbed water.…”
Section: Resultsmentioning
confidence: 84%
“…The existence of imidazolinium‐based ionic moieties is confirmed by the bands at 1670 and 1560 cm −1 , which are typical C=N stretching vibrations of imidazole . The band at 1719 cm −1 in the IR spectrum of I COOH HCP is ascribed to the characteristic C=O stretching vibration of the carboxyl group . The enhanced band at 3388 cm −1 in the IR spectrum of I OH HCP may include the contribution of surface OH groups and the adsorbed water.…”
Section: Resultsmentioning
confidence: 84%
“…39,57 By full evaluation of the catalytic activities in TOF values, VIP-Br is considered as the ideal heterogeneous catalyst that can achieve the high yield (99%) and the highest TOF value (0.453 h À1 ) under the optimal condition (i.e., 1 bar CO 2 , 60 C, 48 h). These satisfactory catalytic results are superior to many reported metal-free ionic polymers (IPs) 15,16,27,28,34,35 and even surpass to some IPs with electrophiles (metal sites) [58][59][60][61] or task-specic HBD groups (such as hydroxyl, 28,57,62 silanols, 17,32,39 carboxylic acids, 63 and ureas 18 ) (see Table S3 † for details). Besides, it is worthy to note that the HBD cocatalyst Hbonded water molecules in VIP-Br play a vital role in activating and enhancing the CO 2 /ECH coupling by forming Hbonds with the oxygen atom of ECH.…”
Section: Entrymentioning
confidence: 88%
“…A series of quaternary ammonium-based ionic polymers synthesised via the Menschutkin reaction were also developed by Wasers et al (Figure 21). 168 They exhibited good activity for the synthesis of cyclic carbonates from aromatic and aliphatic epoxides and carbon dioxide at 1 bar pressure and 120 o C using 0.5 mol% of ionic sites with reaction times of 4-10 h. In 2018, a carboxylic acid functionalised pyridinium-based porous organic framework (POF) based catalyst, POF-PNA-X (X = Cl, Br Please do not adjust margins Please do not adjust margins or I), was developed by Shi et al 169 SEM images showed that both POF-PN and POF-PNA-Br were composed of regular sphere-shaped agglomerates. As the acid groups functioned as hydrogen bond donor sites during the reaction of epoxides with carbon dioxide, the reaction occurred under mild conditions (40 o C, 1 bar of carbon dioxide, 48 h).…”
Section: Ionic Polymersmentioning
confidence: 99%